The Effects of Whole Body Vibration on the Limits of Stability in Adults With Subacute Ankle Injury - Sonia Young; Harvey W. Wallmann; Kailey L. Quiambao; Brooke M. Grimes (International Journal of Sports Physical Therapy)
# Background